2016
DOI: 10.1016/j.kint.2015.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute kidney injury on distant organ function: recent findings and potential therapeutic targets

Abstract: Acute kidney injury (AKI) is a common complication in critically ill patients and subsequently worsens outcomes. Although many drugs to prevent and treat AKI have shown benefits in preclinical models, no specific agent has been shown to benefit AKI in humans. Moreover, despite remarkable advances in dialysis techniques that enable management of AKI in hemodynamically unstable patients with shock, dialysis-requiring severe AKI is still associated with an unacceptably high mortality rate. Thus, focusing only on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
140
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 192 publications
(143 citation statements)
references
References 150 publications
(173 reference statements)
3
140
0
Order By: Relevance
“…Rhabb et al (111) showed that germfree mice have increased susceptibility to ischemia and reperfusion injury (IRI), which is reversed by colonization with commensal bacteria. This observation suggests that certain gut microbiota products might be protecting against IRI (112).…”
Section: Modulation Of Gut Microbiotamentioning
confidence: 99%
“…Rhabb et al (111) showed that germfree mice have increased susceptibility to ischemia and reperfusion injury (IRI), which is reversed by colonization with commensal bacteria. This observation suggests that certain gut microbiota products might be protecting against IRI (112).…”
Section: Modulation Of Gut Microbiotamentioning
confidence: 99%
“…Furthermore, apoptosis within the renal parenchyma exerts profound untoward effects, including apoptosis in distant organs, 158 including the brain, lung, liver, and heart. [78][79][80][159][160][161] It is likely that apoptosis (and perhaps necrosis) occurring outside the kidney is mediated by BCL-2 proteins and may be amenable to systemic manipulation directed at preventing conformational bax activation and/or the decrease in bcl-2 caused by renal stress.…”
Section: Bcl-2 Proteins In Renal Cell Death: a Unified Hypothesis?mentioning
confidence: 99%
“…Focusing only on kidney damage may not be sufficient to improve outcomes of patients with AKI. Recent studies have elucidated complex organ interactions in AKI between the kidneys and distant organs [15]. We further need to identify unrecognized organ interactions in AKI, such as mitochondria injury in the heart, to develop novel therapeutics against AKI and decrease the high mortality rate during AKI-related multiple organ failure.…”
Section: Perspectivesmentioning
confidence: 99%